Ultrahigh lattice thermal conductivity in topological semimetal TaN caused by a large acoustic-optical gap. (15th February 2018) - Guo, San-Dong; Liu, Bang-Gui
Abstract: Topological semimetals may have potential applications such as in topological qubits, spintronics and quantum computations. Efficient heat dissipation is a key factor for the reliability and stability of topological semimetal-based nano-electronics devices, which is closely related to high thermal conductivity. In this work, the elastic properties and lattice thermal conductivity of TaN are investigated using first-principles calculations and the linearized phonon Boltzmann equation within the single-mode relaxation time approximation. According to the calculated bulk modulus, shear modulus and C 44, TaN can be regarded as a potential incompressible and hard material. The room-temperature lattice thermal conductivity is predicted to be 838.62 W   m − 1   K − 1 along the a axis and 1080.40 W   m − 1   K − 1 along the c axis, showing very strong anisotropy. It is found that the lattice thermal conductivity of TaN is several tens of times higher than other topological semimetals, such as TaAs, MoP and ZrTe, which is due to the very longer phonon lifetimes for TaN than other topological semimetals. The very different atomic masses of Ta and N atoms lead to a very large acoustic-optical band gap, and then prohibit the scattering between acoustic and optical phonon modes, which gives rise to very long phonon lifetimes. Calculated results show that isotope scattering has little effect on lattice thermal conductivity, and that phonons with mean free paths larger than 20 (80) μ m along the c direction at 300 K have little contribution to the total lattice thermal conductivity. This work implies that TaN-based nano-electronics devices may be more stable and reliable due to efficient heat dissipation, and motivates further experimental works to study lattice thermal conductivity of TaN.